Analytical Method Validation of High Performance Liquid Chromatography for Ketoconazole Tablets - Lumakso, Fajar Aji; Annisa, Viviane; Alviansyah, Muhammad Rizal; Chabib, Lutfi (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Ketoconazole is an azole antifungal with low solubility and classified as Biopharmaceutical Classification System (BCS) Class II. A tablet formulation based on an alginate-acacia gum matrix is developed to enhance the solubility of ketoconazole. This study aims to validate the analytical method using High-Performance Liquid Chromatography (HPLC) for the assay of ketoconazole in these tablet formulations. The analysis was performed using a C18 column (250×4.6 mm, 5 μm) with a mobile phase consisting of water for injection (WFI) containing 0.15% TEA (pH 3.3) and acetonitrile (50:50 v/v), flow rate 1.0 mL/min, and detection at 232 nm. Method validation included system suitability testing, linearity, accuracy, precision, specificity, LOD, and LOQ. Specificity testing indicated no interference at the retention time of ketoconazole. Good linearity was achieved over 10–250 ppm (r = 0.9996), with good accuracy (99.8–101.75%) and precision (intraday and interday; %RSD < 2%). LOD and LOQ were 2.357 ppm and 7.142 ppm, respectively. The developed HPLC method was shown to be valid, accurate, precise, selective, and reliable for the assay of ketoconazole in tablets formulated with an alginate-acacia gum matrix. This method can be used for routine quality control.